Mother and children outside rural hut with waterwheel (1868)
A photographic glass-plate transparency; part of a set of colour-tinted transparencies depicting life in Japan ca. 1910, including scenery, street scenes, workers, farming, fishing, silk production, stone carvers, wood carvers, metal workers, potters, and artists.